Pengaruh Brand Image, Kualitas Produk dan Harga Terhadap Kepuasan Pelanggan Billy Bakery Sorong - Cabelita sentiwa konjol (Ikatan Da'i Indonesia, 2025)
This study aims to analyze the influence of brand image, product quality, and price on customer satisfaction at Billy Bakery in Sorong City. A quantitative approach was used with an explanatory method. Data were collected using questionnaires distributed to 100 respondents who are customers of Billy Bakery, and analyzed using multiple linear regression. The results show that brand image, product quality, and price each have a positive and significant effect on customer satisfaction. Simultaneously, these three variables also have a significant influence, with a coefficient of determination (R²) of 0.910, indicating that 91% of the variation in customer satisfaction can be explained by the three independent variables. Among them, product quality was found to be the most dominant factor affecting customer satisfaction. These findings provide important implications for Billy Bakery’s marketing strategies to enhance customer satisfaction and loyalty through strengthening brand image, improving product quality, and setting prices aligned with perceived customer value.